Beyond Price and Quality: The Dominance of Brand Image in Thrifting Consumer Behavior - Ferrinadewi, Erna; Nathanael, Jerry (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
In the last decade, the phenomenon of thrifting or the consumption of secondhand fashion has experienced a significant increase in various major cities in Indonesia, especially among the younger generation of urbanites. This culture is no longer just an alternative economic activity, but has become a style. This study aims to analyze the influence of price perception, quality perception, and brand image on purchasing decisions for imported thrifting products in Surabaya. Based on the phenomenon of high consumer interest in purchasing thrifting products to date and the still inconsistent findings related to the influence of Brand Image. The research method used is a mixed methods sequential explanatory, starting with a quantitative approach through a survey of 57 respondents aged 17–65 years who have purchased thrifting products, followed by a qualitative approach in the form of in-depth interviews with five selected informants. Quantitative data were analyzed using multiple linear regression, while qualitative data were analyzed with content analysis. The results showed that only the brand image variable had a positive and significant effect on purchasing decisions (β = 0.748; p < 0.05), while price perception and quality perception did not have a significant effect. Qualitative findings reveal that brand image influences purchasing decisions because it satisfies psychological needs, builds perceptions of exclusivity, and reinforces positive consumer image. The implications of this research emphasize the importance of brand image-based marketing strategies in the import thrifting industry.